Understanding the rulings on greetings and prayers for non-Muslims in Selangor: an analytical study - Shamsul Bahrin, Khairul Falah; Mat Jubri@Shamsuddin, Mustafa (Penerbit UiTM, 2024)
Issues such as conveying Rest in Peace (RIP) for non-Muslims have always been discussed among the community. Recognizing the diverse cultural and religious landscape in Selangor, the research aims to uncover the attitudes and experiences of Muslims and non-Muslims towards these religious practices. This study investigates how Muslim and non-Muslim residents in Selangor, Malaysia, perceive and respond to greetings and prayers in Muslim-majority communities. Using a mixed-methods approach, the study combines qualitative and quantitative surveys to gather data from a representative sample of Muslim and non-Muslim individuals living in Selangor. The qualitative method is used to review the literature and scholars' opinions from classical and contemporary sources. The quantitative surveys aim to quantify the prevalence and variability of these experiences within the broader Muslim and non-Muslim population. By exploring factors such as cultural background, personal beliefs, and interfaith interactions, this research seeks to foster mutual understanding and respect among different communities. It offers recommendations for policymakers, religious leaders, and community members to promote inclusivity and harmony between Muslims and non-Muslims in Selangor. The findings contribute to the existing knowledge on interfaith relations and multiculturalism, shedding light on how greetings and prayers impact non-Muslim individuals. This research encourages dialogue and aims to bridge the gap between religious and cultural communities, ultimately fostering social cohesion and interfaith harmony in Selangor, in particular, and Malaysia, in general.